A missed research opportunity for effective prevention: Clery Act Timely Warning Notices. Issue 5 (22nd June 2022) - Sulzer, Sandra H.; Kimmitt, Joanna Messer; Steel, Maya Miyairi; Jones, Shantoyia; Smith, Tia; Loos, Hayley May; DeRito, Amanda; Redmond, Cleve
Abstract: The Clery Act was created to provide transparency around campus safety, including sexual assault. This includes making timely warnings to the campus community about safety threats on campus. While all universities are mandated to follow the Clery Act, the legislation does not provide guidance on what language universities should employ, how much leeway an institution has in determining if a sexual assault represents an immediate public safety threat, or recommended best practices for Timely Warning Notices. The need for guidance is evident to address timeliness, language, and prevention science. Victim blaming, racial/ethnic stereotypes and LGBTQ + inclusivity can all be implied through the nature of recommendations that colleges offer. Language matters, especially when timely warnings are one of the few forms of communication a university sends to everyone affiliated with their institution. We provide recommended next steps for researching timely warnings as a sexual assault prevention tool.